Descriptive study of endoscope assisted creation of neoturbinate by antral mucosal inversion in atrophic rhinitis - Kedarnath, Ratkal; Mushtaq, Syed (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: As the exact etiology is not known, treatment is directed towards symptomatic relief. Medical treatment leads only to temporary remission of symptoms. Over the years, surgeons have attempted various techniques for long term relief of symptoms. Most of the techniques have been directed to the narrowing of the nasal cavity. Methods: All the cases diagnosed as primary atrophic rhinitis and who were willing to undergo this surgery were taken for the study. The cases diagnosed as primary atrophic rhinitis were subjected to detailed history and examination. Clinically following conditions were ruled out – tuberculosis, syphilis, rhinoscleroma, leprosy. A routine haemogram (Hb%, TC, DC, BT, CT), urine examination (albumin, sugar, microscopy), ESR serum VDRL was done for the patients. Results: We were successful in creating a neoturbinate in 12 patients in our study. Of these, majority of the patients (6 patients) had their duration of symptoms between 2-4 years, the outcome in them are excellent in 4 patients, good in 2 patients. Conclusions: The results are encouraging with reduced crusting, healthier mucosa and some patients even regaining their sense of smell. All these above, with no nasal obstruction or pinched nostrils as may occur in young’s closure. But the effort involved is more in this surgical procedure.